2005
DOI: 10.1016/j.ijgo.2005.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Oral misoprostol for prevention of postpartum hemorrhage by paramedical workers in India

Abstract: Simple interventions can be easily implemented in rural health care settings to reduce the blood loss during labor. This finding has significant implications for developing countries, in which the prevalence of anemia is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 19 publications
7
41
2
Order By: Relevance
“…Table 6 reviews studies examining the use of misoprostol in the prevention of PPH in community and hospital settings. Despite the relative superiority of conventional injectable uterotonics, to date nobody has rejected misoprostol as an appropriate drug where injectable uterotonics are not available or cannot be administered [43,[45][46][47][48][49][50][51][52]. Furthermore, systematic reviews of randomized controlled trials found decreased need for additional uterotonics when comparing misoprostol to placebo, and recommend misoprostol to be used in developing countries [45,51,52].…”
Section: Postpartum Hemorrhagementioning
confidence: 99%
“…Table 6 reviews studies examining the use of misoprostol in the prevention of PPH in community and hospital settings. Despite the relative superiority of conventional injectable uterotonics, to date nobody has rejected misoprostol as an appropriate drug where injectable uterotonics are not available or cannot be administered [43,[45][46][47][48][49][50][51][52]. Furthermore, systematic reviews of randomized controlled trials found decreased need for additional uterotonics when comparing misoprostol to placebo, and recommend misoprostol to be used in developing countries [45,51,52].…”
Section: Postpartum Hemorrhagementioning
confidence: 99%
“…It is well absorbed when administered by oral, vaginal, sublingual, rectal, and buccal routes. Oral [3][4][5][6][7][8] and rectal [9,10] administration of misoprostol has been found to be effective in preventing and controlling PPH in various studies. Although misoprostol has been included recently in the WHO essential medicine list, the lowest effective dose and the optimal route of administration for maximum benefit and minimum adverse effects is yet to be established [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The drug's low cost, ease of administration through multiple routes, stability, and safety profile make it a good option in resource-poor settings [5][6][7], and in patients who are vomiting, unable to take medications, or under anesthesia [2]. The use of misoprostol to prevent [6,8,9] or treat [10,11] PPH has been reported repeatedly in the literature. The aim of the present study was to compare, in a low-resource setting, the efficacy of 800 μg of rectal misoprostol and 5 IU of oxytocin as an intravenous infusion, as prophylaxis against PPH.…”
Section: Introductionmentioning
confidence: 99%